2018
DOI: 10.1155/2018/2458679
|View full text |Cite
|
Sign up to set email alerts
|

The Rising Era of Immune Checkpoint Inhibitors in Myelodysplastic Syndromes

Abstract: Myelodysplastic syndromes (MDS) are a heterogeneous group of diseases characterized by ineffective hematopoiesis and a wide spectrum of manifestations ranging from indolent and asymptomatic cytopenias to acute myeloid leukemia (AML). MDS result from genetic and epigenetic derangements in clonal cells and their surrounding microenvironments. Studies have shown associations between MDS and other autoimmune diseases. Several immune mechanisms have been identified in MDS, suggesting that immune dysregulation might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 55 publications
(67 reference statements)
0
15
1
Order By: Relevance
“…Unlike solid tumors where TMB and/or programmed death ligand 1 (PD-L1) expression have been validated as biomarkers to identify patients who may benefit from ICI, their utility in AML and MDS is yet to be established [ 24 ]. Nevertheless, several studies have reported benefit of ICI in combination with standard therapies including hypomethylating agents in AML and MDS, though the mechanism appears to be enhancement of graft-versus-tumor effect and is independent of TMB [ 25 , 26 ]. Cut-off values for TMB vary considerably across histological types of malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike solid tumors where TMB and/or programmed death ligand 1 (PD-L1) expression have been validated as biomarkers to identify patients who may benefit from ICI, their utility in AML and MDS is yet to be established [ 24 ]. Nevertheless, several studies have reported benefit of ICI in combination with standard therapies including hypomethylating agents in AML and MDS, though the mechanism appears to be enhancement of graft-versus-tumor effect and is independent of TMB [ 25 , 26 ]. Cut-off values for TMB vary considerably across histological types of malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, immune regulation within the bone marrow is a complex interplay between T-cells, mesenchymal stromal cells, myeloid-derived suppressor cells, and various soluble factors. These interactions are highly complex and have been reviewed in detail elsewhere 18,41,42 .…”
Section: ) Introductionmentioning
confidence: 99%
“…Aberrant immune function and dysregulation of immune checkpoint (IC) molecules represent a known pathophysiological aspect of MDS, providing the rationale for studying the role of IC inhibitors (ICI) in those patients, especially after HMA failure [ 122 , 123 , 124 ].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%